Consumo m??ximo de oxig??nio, validade de equa????es de predi????o e poss??vel influ??ncia do polimorfismo I/D do gene da ECA sobre sua determina????o - Almeida, Jeeser Alves de (2011)
Predictive equations have been widely used to determine indirect maximal oxygen uptake (VO2max) as it can evaluate a large number of people with low cost and, in most cases, nearing the specificity of some sports. However, the VO2max can be influenced by various environmental and genetic factors, the validity of these equations on estimating VO2max of young brazilians should be further studied. This investigation includes two studies with young physically active brazilians. The first one evaluated the validity of a predictive equation proposed by Cureton et al., (1995) in estimating VO2max from the 1600m running performance, and also to suggest a new and specific predictive equation for physically active brazilians. . The second study examined the possible influence of I/D polymorphism of ACE genotype on determining the real and predicted VO2max in these participants. For the study I thirty young and physically active underwent both to a 1600m running test and an incremental cardiopulmonary exercise test (IT) on a treadmill with analysis of expired gases. The participants were divided into two groups (G1 and G2) being that in G1 the new equation was generated (Simples linear regretion between mean velocity at 1600m and VO2max) while its validity was examined in G2. When applied on the results of G2, a One Way ANOVA showed no statistical difference and a high correlation between VO2max obtained by the predictive equation generated in G1 [VO2max = (0.177 * 1600Vm) + 8.101] with the values of IT (50.1 ??7.2 mL.kg-1.min-1 vs 50.1 ??7.1 mL.kg-1.min-1) (P>0.05) (R = 0.81). However the VO2max results determined from equation of Cureton et al., (1995) [VO2peak = -8.41 (MRW) +0.34 (MRW) 2 + 0.21 (Age x Gender) ??? 0.84 (BMI) + 108.94] (44.2?? 6.5mL.kg-1.min-1) differed from both IT and the values obtained from the new proposed equation (P<0.05). The concordance between methods was confirmed by Bland and Altman technique. For the study 2, 57 participants underwent the same procedures as study 1, but had their DNA extracted and were genotyped for the insertion/deletion (I/D) polymorphism of the ACE gene. The participants were separated into three groups accordingly to the I/D polymorphism of ACE gene (being allocated either in DD, ID, or II group). The results revealed significantly lower 1600m velocity as well as VO2max for DD carriers compared to II and ID individuals (45.6 ??1.81 mL.kg-1.min-1 vs 51.9 ?? 0.79 mL.kg-1.min-1 vs 54.4 ?? 0.96 mL.kg-1.min-1) (P <0.01). On the other hand, a within-group analysis revealed that VO2max obtained in IT did not differ from that calculated by the equation generated in Study I. Moreover, the equation generated in Study I was considered valid for estimating the VO2max in physically active young adults through a 1600m running test despite of being II, ID or DD carrier. Although the influence of I/D polymorphism of ACE gene on VO2max and middle distance performance , the accuracy of the proposed equation on predicting VO2max did not suffer interference from the I/D polymorphism of the ACE gene.